Chinese Computational Linguistics c - Sun, Maosong; Huang, Xuanjing; Ji, Heng.; Liu, Zhiyuan; Liu, Yang.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book constitutes the proceedings of the 18th China National Conference on Computational Linguistics, CCL 2019, held in Kunming, China, in October 2019. The 56 full papers presented in this volume were carefully reviewed and selected from 134 submissions. They were organized in topical sections named: linguistics and cognitive science, fundamental theory and methods of computational linguistics, information retrieval and question answering, text classification and summarization, knowledge graph and information extraction, machine translation and multilingual information processing, minority language processing, language resource and evaluation, social computing and sentiment analysis, NLP applications.
Colligational Patterns in China English: the Case of the Verbs of Communication -- Testing the Reasoning Power for NLI Models with Annotated Multi-perspective Entailment Dataset -- Enhancing Chinese Word Embeddings from Relevant Derivative Meanings of Main-Components in Characters -- Association Relationship Analyses of Stylistic Syntactic Structures -- BB-KBQA: BERT-Based Knowledge Base Question Answering -- ERCNN: Enhanced Recurrent Convolutional Neural Networks for Learning Sentence Similarity -- Improving a Syntactic Graph Convolution Network for Sentence Compression -- Comparative Investigation of Deep Learning Components for End-to-end Implicit Discourse Relationship Parser -- Syntax-Aware Attention for Natural Language Inference with Phrase-Level Matching -- Sharing Pre-trained BERT Decoder for a Hybrid Summarization -- Title-Aware Neural News Topic Prediction -- How to Fine-Tune BERT for Text Classification? -- A Comprehensive Verification of Transformer in Text Classification -- Improving Relation Extraction with Relation-Based Gated Convolutional Selector -- Attention-based Gated Convolutional Neural Networks for Distant Supervised Relation Extraction -- Relation and Fact Type Supervised Knowledge Graph Embedding via Weighted Scores -- Leveraging Multi-Head Attention Mechanism to Improve Event Detection -- Short-Text Conceptualization Based on A Co-Ranking Framework via Lexical Knowledge Base -- Denoising Distant Supervision for Relation Extraction with Entropy Weight Method -- Cross-view Adaptation Network for Cross-domain Relation Extraction -- Mongolian-Chinese Unsupervised Neural Machine Translation with Lexical Feature -- Learning Multilingual Sentence Embeddings from Monolingual Corpus -- Chinese Historical Term Translation Pairs Extraction Using Modern Chinese As a Pivot Language -- Construction of an English-Uyghur WordNet Dataset -- Endangered Tujia Language Speech Enhancement Research Based on Improved DCGAN -- Research for Tibetan-Chinese Name Transliteration Based on Multi-granularity -- An End-to-end Method for Data Filtering on Tibetan-Chinese Parallel Corpus via Negative Sampling -- An Attention-Based Approach for Mongolian News Named Entity Recognition -- On the Semi-unsupervised Construction of Auto-Keyphrases Corpus from Large-scale Chinese Automobile E-Commerce Reviews -- Multi-label Aspect Classification on Question-Answering Text with Contextualized Attention-based Neural Network -- A Document Driven Dialogue Generation Model -- Capsule Networks for Chinese Opinion Questions Machine Reading Comprehension -- Table-to-Text Generation via Row-Aware Hierarchical Encoder -- Dropped Pronoun Recovery in Chinese Conversations with Knowledge-enriched Neural Network -- Automatic Judgment Prediction via Legal Reading Comprehension -- Legal Cause Prediction with Inner Descriptions and Outer Hierarchies -- Natural Language Inference based on the LIC Architecture with DCAE Feature -- Neural CTR Prediction for Native Ad -- Depression Detection on Social Media with Reinforcement Learning -- How Important is POS to Dependency Parsing? Joint POS Tagging and Dependency Parsing Neural Networks -- Graph Neural Net-based User Simulator -- Pinyin as A Feature of Neural Machine Translation for Chinese Speech Recognition Error Correction -- Neural Gender Prediction from News Browsing Data -- A Top-down Model for Character-level Chinese Dependency Parsing -- A Corpus-free State2Seq User Simulator for Task-oriented Dialogue -- Utterance Alignment in Custom Service by Integer Programming.
Keywords: Natural language processing (Computer science).; Machine learning; Robotics; Data mining; Natural Language Processing (NLP).; Machine Learning; Robotics; Data Mining and Knowledge Discovery